2018
DOI: 10.5194/tc-12-675-2018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms influencing seasonal to inter-annual prediction skill of sea ice extent in the Arctic Ocean in MIROC

Abstract: Abstract. To assess the skill of seasonal to inter-annual predictions of the detrended sea ice extent in the Arctic Ocean (SIE AO ) and to clarify the underlying physical processes,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 45 publications
4
12
0
Order By: Relevance
“…Note that loading due to sea ice and accumulated snow on sea ice are removed from the model sea level height and that the global mean value is eliminated. sistent with previous modeling studies that reported the importance of the well-resolved stratosphere for better simulation of stratospheric variability (e.g., Cagnazzo and Manzini, 2009;Charlton-Perez et al, 2013;Osprey et al, 2013). In December-January, however, MIROC6 still underestimates the frequency of SSW events, which is a common bias in other high-top climate models (e.g., Inatsu et al, 2007;Charlton-Perez et al, 2013;Osprey et al, 2013).…”
Section: Stratospheric Circulationsupporting
confidence: 76%
See 1 more Smart Citation
“…Note that loading due to sea ice and accumulated snow on sea ice are removed from the model sea level height and that the global mean value is eliminated. sistent with previous modeling studies that reported the importance of the well-resolved stratosphere for better simulation of stratospheric variability (e.g., Cagnazzo and Manzini, 2009;Charlton-Perez et al, 2013;Osprey et al, 2013). In December-January, however, MIROC6 still underestimates the frequency of SSW events, which is a common bias in other high-top climate models (e.g., Inatsu et al, 2007;Charlton-Perez et al, 2013;Osprey et al, 2013).…”
Section: Stratospheric Circulationsupporting
confidence: 76%
“…Seasonal to decadal climate predictions are also of significant concern. By initializing prognostic variables in our climate models using observation-based data (Tatebe et al, 2012), significant prediction skills in several specific phenomena, such as the El Niño-Southern Oscillation (ENSO) and the Arctic sea ice extent on seasonal timescales, the Pacific Decadal Oscillation (PDO; Mantua et al, 1997), the Atlantic Multi-decadal Oscillation (AMO; Schlesinger and Ramankutty, 1994), and the tropical transbasin interactions between the Pacific and the Atlantic on decadal timescales, are detected (e.g., Mochizuki et al, 2010;Chikamoto et al, 2015;Imada et al, 2015;Ono et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…June nual variability, the temperature and salinity of the Atlantic inflows to the Arctic Ocean show also pronounced decadal to multidecadal variability (Zhang, 2015). This aligns with the concept of different previous studies, which suggest that the decreasing trend in the Arctic sea ice is partially driven by AMO (Park and Latif, 2008;Lindsay et al, 2005;Ding et al, 2014;Yu et al, 2017). Moreover, starting at the beginning of 1990s, the AMO switched to a positive phase, at the same time when the Arctic sea ice extent started its abrupt decline.…”
Section: May Datasupporting
confidence: 90%
“…1 and 5), thus contribut-ing to the skill of our forecast. The OHC anomalies form the North Atlantic flow into the Arctic basin, via advection, and affect the sea ice distribution (Polyakov et al, 2017;Ono et al, 2018). In a recent study, Yu et al (2017) have shown that the leading mode of variability of global sea ice concentration is positively correlated with the AMO and negatively correlated with the PDO.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research includesPetty et al (2017),Ono et al (2018),Serreze and Meier (2019),and Ionita et al (2019). Ongoing prediction research forums include the Sea Ice Prediction Network at https://www.…”
mentioning
confidence: 99%